Nitridation of γ-TiAl alloys by direct metal-gas reaction at 1000-1300 K - Thongtem S. (2014)
Two γ-TiAl alloys, Ti-47at%Al-2at%Nb-2at%Cr (MJ12) and Ti-47at%Al-2at%Nb-2at%Mn-0.8at%TiB2 (MJ47), were nitrided by direct metal-gas reaction at 1000-1300 K in 10 cm3s-1NH 3. X-ray diffraction revealed formation of TiN at 1100-1300 K. Knoop microhardness values of the alloys were increased with an increase in the nitridation temperature. Microhardness values of MJ12 and MJ47 with 1300 K nitridation were respectively improved to 1.65 and 1.38 times those of the controls. Nitridation depth at a variety of temperature determined by Rutherford backscattering spectrometry was increased with an increase in the temperature. Ti, Al and N concentrations at a variety of depths analysed by scanning electron microscopy and energy dispersive X-ray linescanning are also explained. Copyright © 2005 John Wiley & Sons, Ltd.